2002
DOI: 10.1016/s0005-2736(02)00454-6
|View full text |Cite
|
Sign up to set email alerts
|

Band-3 protein function in human erythrocytes: effect of oxygenation–deoxygenation

Abstract: Sulfate transport by band-3 protein in adult human erythrocytes was shown to be modulated by oxygen pressure. In particular, a higher transport activity was measured under high oxygen pressure than at low one (0.0242+/-0.0073 vs. 0.0074+/-0.0010 min(-1)). Other factors, such as magnesium ions and orthovanadate, which can indirectly affect the binding properties of the cytoplasmic domain of band 3 (cdb3), influence significantly the anion exchanger activity. No effect of oxygen pressure on sulfate transport was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…For instance, comparison of the kinetics of band 3-mediated Cl-transport in fish (carp, rainbow trout, eel and cod) and human erythrocytes did not reveal a significant difference between oxygenated and deoxygenated RBCs in the species studied [33]. Nor was O 2 -dependence of the anion exchanger revealed in crocodilian [34] and chicken [35] RBCs. On the other hand, there are recent reports that in normal human red cells, oxygenation stimulates the anion exchanger [35,36].…”
Section: +mentioning
confidence: 99%
“…For instance, comparison of the kinetics of band 3-mediated Cl-transport in fish (carp, rainbow trout, eel and cod) and human erythrocytes did not reveal a significant difference between oxygenated and deoxygenated RBCs in the species studied [33]. Nor was O 2 -dependence of the anion exchanger revealed in crocodilian [34] and chicken [35] RBCs. On the other hand, there are recent reports that in normal human red cells, oxygenation stimulates the anion exchanger [35,36].…”
Section: +mentioning
confidence: 99%
“…Our previous work highlighted that in adult human erythrocytes sulphate transport across the membrane is modulated by the pressure of oxygen and therefore by the oxygen-linked transition of Hb [17]. The same study performed on pig erythrocytes is shown in Figure 1 and Figure 2.…”
Section: Resultsmentioning
confidence: 61%
“…We have already discussed the involvement of the conformational transition (T-R) of Hb on the different activities of human B3 in HOS and LOS state. We associated this finding with the structural hindrance caused by the gradual increase of Hb bound to cdb3 that would take place on passing from HOS to LOS [17] [26]. In the case of pig RBCs (Figure 2), the stronger involvement of Hb in the modulation of B3 could be affected by the contribution of free Cl − which is lower in the LOS state as consequence of the binding to Hb.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…AE1 is found in erythrocytes and the kidneys, AE2 is found in a wide range of tissues, and AE3 is found in the brain, retina and heart. All members of the anion exchanger family have two domains: an N-terminal cytoplasmic domain that contains binding sites for glycolytic enzymes and hemoglobin; and a C-terminal membrane domain [8,9]. The membrane domain is highly conserved.…”
Section: Introductionmentioning
confidence: 99%